Cysteine challenge test as a novel diagnostic tool to distinguish oral halitosis. (17th November 2021) - Aydin, Murat; Gunay, Ismail
Abstract: Background: The cysteine challenge test is often used to check the H2 S production capacity of the mouth. Patients with oral halitosis group (n = 305) or non‐oral halitosis group (n = 191) and healthy individuals (control group, n = 102) were compared with each other to identify any possible relationship between initial and cysteine‐induced oral H2 S concentrations. Subjects and Method: The medical records of 598 participants were reviewed retrospectively. Oral H2 S concentrations before (pre‐CR) and after cysteine rinse (post‐CR) with 5 mL of 20 mmol L‐ cysteine solution for 30 s were compared. Results: Pre‐CR H2 S concentrations were >0.8 ppm in 75.1% of oral group patients but less than <0.8 ppm in 87.3% of the non‐oral group and 86.9% of controls. After cysteine rinse, oral H2 S concentrations exceeded 12 ppm in 72% of the oral halitosis patients but were lower in 88% of non‐oral group and 99% of controls. Whilst post‐CR/pre‐CR ratio was >12 in 74.5% of the oral group, it was <12 in 81.7% of the non‐oral group and 83.4% of controls. Conclusion: Cysteine challenge test can be used as a diagnostic tool to identify an individual's tendency to produce oral malodor, not only to quantify momentary halitosis level.